2010
DOI: 10.1007/jhep06(2010)016
|View full text |Cite
|
Sign up to set email alerts
|

On the non-BPS string solutions in Sasaki-Einstein gauge/gravity duality

Abstract: We present an extensive analysis on several string solutions in AdS 5 × Y p,q and find some interesting properties of their energy-spin relations. Their energy depends always on the parameter a(p, q) which characterizes these manifolds. The range of this parameter for the string solutions is constrained by the Sasaki-Einstein constraints that the solutions should satisfy. Hence some string solutions we find are not valid for the whole class of Y p,q manifolds. For some of our solutions, when the maximum allowe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The string solutions again show chaotic behavior implying nonintegrability of the corresponding sigma models. However, in Y p,q manifolds special care should be taken with the string solution to show that indeed they satisfy the Sasaki-Einstein constraints as in [15,16,17]. More recently it has been shown that integrability is not present in marginal complex β-deformations [18].…”
Section: Introduction and Methodsmentioning
confidence: 99%
“…The string solutions again show chaotic behavior implying nonintegrability of the corresponding sigma models. However, in Y p,q manifolds special care should be taken with the string solution to show that indeed they satisfy the Sasaki-Einstein constraints as in [15,16,17]. More recently it has been shown that integrability is not present in marginal complex β-deformations [18].…”
Section: Introduction and Methodsmentioning
confidence: 99%
“…This implies that the system of equations (28), (29) and (34) becomes the same as the corresponding system of equations in the undeformed theory N = 4 sYM but with the redefined angle ∆θ ef f in the place of the angle ∆θ S 5 , where in the undeformed theory ∆θ S 5 is the angle of the cusp in the internal space. Calculating the expression for the quark anti-quark potential in the deformed theory we see that it depends only on y 1 and the turning point of the string y 2 and not on c 1 andγ explicitly.…”
Section: The Marginally Deformed Gauge/gravity Dualitymentioning
confidence: 99%
“…This value of y leads to important simplifications and although this is a limiting example, since it is a very special point in our manifold we examine if the full solution exist for completeness. The third equation of (22) and the last equation of (23) using the fact that J α = 0 giveṡ…”
Section: Bps Solutionsmentioning
confidence: 99%
“…It turns outs that the equations (22) and the last equation of (23) are satisfied as well as the first equation of motion (60). The equation (61) however introduces a relation between the deformation parameterγ and the coordinate y, and this implies that a BPS string solution for a fixed deformation parameterγ, exist only in a particular Sasaki-Einstein manifold.…”
Section: Bps Solutionsmentioning
confidence: 99%
See 1 more Smart Citation